2019
DOI: 10.1007/s00204-019-02565-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of a multi-layer systems toxicology framework for in vitro assessment of the biological effects of Classic Tobacco e-liquid and its corresponding aerosol using an e-cigarette device with MESH™ technology

Abstract: We previously proposed a systems toxicology framework for in vitro assessment of e-liquids. The framework starts with the first layer aimed at screening the potential toxicity of e-liquids, followed by the second layer aimed at investigating the toxicity-related mechanism of e-liquids, and finally, the third layer aimed at evaluating the toxicity-related mechanism of the corresponding aerosols. In this work, we applied this framework to assess the impact of the e-liquid MESH Classic Tobacco and its aerosol com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…A specific point of consistency between the effects of Base ECV on human immature and LPS-matured MoDCs in the present study, and on buccal epithelial cells in the study of Iskandar et al (Iskandar et al 2019) is that we observed upregulation of inflammatory signalling molecules at 30 min and 24 h and Iskandar et al observed upregulation of an inflammatory transcriptome at 4 h and 24 h. In addition, we observed upregulation by ECVE of the release of IL-6 (but not other cytokines) from LPS-matured DCs, and they observed increased release of IL-1α and IP-10 (but not other cytokines) by buccal cells in response to Base ECV. These different studies thus provide consistent evidence for mild pro-inflammatory effects of Base ECV.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A specific point of consistency between the effects of Base ECV on human immature and LPS-matured MoDCs in the present study, and on buccal epithelial cells in the study of Iskandar et al (Iskandar et al 2019) is that we observed upregulation of inflammatory signalling molecules at 30 min and 24 h and Iskandar et al observed upregulation of an inflammatory transcriptome at 4 h and 24 h. In addition, we observed upregulation by ECVE of the release of IL-6 (but not other cytokines) from LPS-matured DCs, and they observed increased release of IL-1α and IP-10 (but not other cytokines) by buccal cells in response to Base ECV. These different studies thus provide consistent evidence for mild pro-inflammatory effects of Base ECV.…”
Section: Discussionsupporting
confidence: 67%
“…This is consistent with some other studies that have compared the effects of CS and ECV on different cell types. In particular, Iskandar et al (Iskandar et al 2019) recently reported that, in a multi-layer toxicology system, E-liquid and E-vapour were less toxic to cultured airway epithelial cells than was CS. They found that the 'Base' E-liquid that is equivalent to that used in our study (containing the humectants propylene glycol and vegetable glycerin, plus nicotine), and MESH Classic Tobaccoflavoured E-liquid, showed similar levels of toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol deposited mass per puff as well as nicotine and carbonyl concentrations are commonly used for e-cig dosimetry measurement (Adamson et al . 2017 ; Iskandar et al , 2019 ; Bishop et al 2019 ).
Figure 3.
…”
Section: Exposure Systems Used With Ali Airway Culturesmentioning
confidence: 99%
“…To adapt the conventional smoking robots for e-cig research, Vitrocell® VapeStarters are used for activating various ecig products and, therefore, have greatly expanded the range of tobacco products that can be tested with the systems. Aerosol deposited mass per puff as well as nicotine and carbonyl concentrations are commonly used for e-cig dosimetry measurement (Adamson et al 2017;Iskandar et al, 2019;Bishop et al 2019).…”
Section: Exposure Systems Used With Ali Airway Culturesmentioning
confidence: 99%